A Nonlinear Control Design Strategy for Piloting Fixed Wing Aircrafts. Issue 2 (2020) - Hamissi, A.; Busawon, K.; Bouzid, Y.; Zaouche, M.; Hamerain, M.; Melkou, L.
Abstract: This paper proposes a novel nonlinear feedback control strategy for velocity and attitude control of fixed wing aircrafts. The key feature of the control design strategy is the introduction of a virtual control input in order to deal with the underactuation property of such vehicles and to indirectly control the orientaion of the aircraft. As such, the proposed strategy consists of three control loops each realising a specific task. Simulation results on Jetstream-3102 aircraft show very good performance in terms of convergence towards the desired reference trajectories and in terms of robustness with respect to modeling uncertainties.